Brick by brick, block by block: Building a sustainable formalization strategy for small-scale gold mining in Ghana. Issue 135 (September 2022) - Hilson, Gavin; Bartels, Ekow; Hu, Yanfei
Abstract: This paper contributes to the debate on formalization of artisanal and small-scale mining (ASM) – low-tech, labour-intensive mineral extraction and processing – in sub-Saharan Africa, drawing on fresh insights from Ghana. In the early-1990 s, with support from GTZ, the German technical arm, Ghana implemented its Small-Scale Mining Project (SSMP), an institutional framework designed specifically to facilitate legalization of, and administer assistance to, ASM. Whilst at the time of its launch, the SSMP was lauded in donor circles as a best practice governance structure for formalizing ASM in sub-Saharan Africa, its existence was short-lived because of poor planning, uncoordinated execution, and a general lack of commitment on the part of government and donors to fulfilling its objectives. The institutional, policy and regulatory framework that has emerged in its place has stifled formalization of the sector by introducing a number of barriers that have prevented operators from legalizing their activities and accessing crucial support services. Ghana's small-scale miners have long called for the implementation of a more operator-friendly licensing apparatus and support structure, although it is becoming increasingly evident that such change is unlikely to happen without an unprecedented intervention. This, however, may be supplied in the form of the Community Mining Scheme (CMS), launched by Ghana's senior government officials in 2019 in a bid to ringfence specific areas for licensed ASM. Wide adoption of the CMS promises to transform the governance of ASM in Ghana into a more operator-friendly and efficient process by engaging local government units hitherto marginalized in the sector's formalization process; (re)establishing a decentralized platform donors desperately covet to implement projects with greater precision; and revitalizing dormant policy interventions – foremost, the list of Designated Areas for Small Scale Gold & Diamond Mining in Ghana, initiated by the government in May 2009 – that are keys to facilitating a robust grassroots institutional presence for licensing and a galvanized support structure for operators. Highlights: Ghana's pledge to formalize artisanal and small-scale mining (ASM) has entered its fourth decade. Little progress has been made, however, because the country's ASM formalization strategy is highly-centralized. The development of a legalized ASM sector will continue to be elusive in Ghana without decentralized governance and support. The advent of the Community Mining Scheme (CMS), which empowers local government, could facilitate change in the sector. The CMS maps on to and legitimizes other areas of policy, thus fortifying the country's ASM formalization strategy.